Equivalence and polyvalence: A case for the stratification of semantics - Widoff, Andreas (Public Journal of Semiotics, 2022)
The article presents a semantic theory suggesting that equivalence and polyvalence are closely connected phenomena. The connection between them is utilised by making equivalence the basis of an argument for polyvalence within semantics, or in other terms, for a stratified semantics encompassing two levels of description. This argument from equivalence lends new support to frameworks assuming a stratified semantics. For the argument to work properly, it is necessary to distinguish between equivalences that are facts of language and equivalences that depend on extralinguistic circumstances. A few other requirements for a coherent concept of equivalence are also introduced. A major part of the article is devoted to an investigation of previous accounts of equivalence and of the conceptual underpinnings of these accounts. The investigation shows that all previous accounts have failed to make the necessary distinction. Close examination of various cases of equivalence reveals differences that are captured by the proposed distinction, thus providing evidence for its accuracy. The article concludes that the argument from equivalence strengthens the case for a stratified semantics provided that the concept of equivalence has been appropriately delimited and defined.